1956
DOI: 10.1042/bj0640676
|View full text |Cite
|
Sign up to set email alerts
|

Toxic liver injury. The metabolism of dimethylnitrosamine

Abstract: In a previous paper (Barnes & Magee, 1954) dimethylnitrosamine was shown to cause acute centrilobular necrosis of the liver in the rat, mouse, guinea pig, rabbit and dog, when given in doses of the order of 25 mg./kg. body weight. No gross abnormality was found in organs or tissues other than the liver. In long-term feeding experiments, when dimethylnitrosamine was added to the diet of rats at a level of 50 parts per million, a high incidence of malignant hepatic tumours occurred, with no evidence of primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
0
1

Year Published

1962
1962
1978
1978

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 13 publications
6
45
0
1
Order By: Relevance
“…As biochemical effects are only observed after a time-lag (Magee, 1958;Hultin et al 1960), and as decomposition in vivo is substantially confined to the liver, which is the only organ severely affected by acute doses (Magee, 1956), it has generally been assumed that the toxic compound is a metabolite. Formaldehyde (Brouwers & Emmelot 1960), nitrite (Heath & Dutton, 1958) and diazomethane (Rose, 1958;R.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As biochemical effects are only observed after a time-lag (Magee, 1958;Hultin et al 1960), and as decomposition in vivo is substantially confined to the liver, which is the only organ severely affected by acute doses (Magee, 1956), it has generally been assumed that the toxic compound is a metabolite. Formaldehyde (Brouwers & Emmelot 1960), nitrite (Heath & Dutton, 1958) and diazomethane (Rose, 1958;R.…”
mentioning
confidence: 99%
“…Dimethylnitrosamine is decomposed both in vivo (Magee, 1956;Heath & Dutton, 1958) and in vitro (Magee & Vandekar, 1958;Brouwers & Emmelot, 1960;Hultin, Arrhenius, Low & Magee, 1960). As biochemical effects are only observed after a time-lag (Magee, 1958;Hultin et al 1960), and as decomposition in vivo is substantially confined to the liver, which is the only organ severely affected by acute doses (Magee, 1956), it has generally been assumed that the toxic compound is a metabolite.…”
mentioning
confidence: 99%
“…It is probable that the crucial factor is the amount of the carcinogen which reaches the site of action as has been accepted for other drug effects (Brodie, Cosmides and Rall, 1965). In the case of DMN which almost certainly has to be -metabolised before it becomes carcinogenically active it has long been known that -the metabolism of a second dose of DMN is slowed when it follows closely after the first dose (Magee, 1956). Under these circumstances it is easy to visualise an effective dose reaching the kidneys.…”
Section: Discussionmentioning
confidence: 98%
“…The characteristic senile changes (Magee, 1959) were noted in rats which survived for more than a year. In 42 rats enlarged tubules similar to those described by others (Allen, Fisher and Adams, 1964;Foley et al, 1964, andTerracini, Palestro, Gigliardi andMontesano, 1967) were observed.…”
Section: Kidneymentioning
confidence: 95%
“…As a result, renal tumours develop in all animals which survive the initial toxic insult (Hard and Butler, 1970). Because the DMN is eliminated with 24 h of administration (Magee, 1956) and the rat kidney has apparently adopted a neoplastic course within 20 h of injection (Borland and Hard, 1974), this experimental system might permit the monitoring of the earliest detectable in vivo biochemical alterations involved in neoplasia.…”
mentioning
confidence: 99%